PENENTUAN KADAR LEMAK PADA TEPUNG TERIGU DAN TEPUNG MAIZENA MENGGUNAKAN METODE SOXHLET - FARIDA ARIANI; SOFIA ROHANI; NI MADE WIASTY SUKANTY; LINA YUNITA; NOVIA ZURIATUN SOLEHAH; BAIQ IKE NURSOFIA (Universitas Mahasaraswati K. Mataram, 2024)
Fat is one of the important components in food that provides texture and taste. Flour is a food ingredient made from grinding tubers, grains, and stems (sago). This research aimed to determine the difference in fat content in bulk wheat flour (without label), wheat flour (high protein, labeled), and cornstarch. The fat content of a food can be determined by extracting the fat. The fat content analysis method in this research used the Soxhlet method, which can extract fat with the nonpolar organic solvent n-hexane using a soxhlet extractor. The highest fat content was obtained in the wheat flour sample (high protein, labeled) at 2.29%, followed by bulk wheat flour at 1.32%, and cornstarch at 0.65%. The differences of fat content in flour can be caused by the variations of fat content in the raw materials that used in produced flour